Predicting Stock Prices: The Role of Profitability, Operating Performance, Capital Expenditure and Growth Opportunity Before and After Spin-Offs - Apriana, Yulia; Evana, Einde; Syaipudin, Usep (Basecamp Economics PubMed, 2024)
In the last few decades there has been an increase in the number of merger and acquisition (M&A) deals. However, there is a relatively new trend to divest a company's operating activities. This research focuses on spin-off as a divestment method which is defined as the separation of a subsidiary or division from the parent company by creating a new, independent company. The aim of this research is to assess the parent company's share price response to the spin-off announcement and measure the long-term performance of the parent company that is carrying out the spin-off. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2010 - 2023. The sampling technique used was purposive sampling and a sample of 32 companies was obtained with 192 observation consisting of 3 (three) years before the spin-off and 3 (three) years after the spin-off. The analysis method used is multiple linear regression using SPSS Ver 22. The research results show that profitability and growth opportunity influence share prices before the spin-off event, whereas after the spin-off event only the growth opportunity variable influences share prices. The operating performance and capital expenditure variables have no effect on share prices either before the spin-off event or after the spin-off event. The abnormal return value is smaller in the event after the spin-off.